Venus in fur [videorecording (DVD)] - Polanski, Roman; Seigner, Emmanuelle; Amalric, Mathieu, 1965- (Program content, R.P. Productions-Monolith Films ; Package design, MPI Media Group, 2014)
"Alone in a Parisian theatre after a day of auditioning actresses for the play he is preparing to direct, Thomas is complaining over the phone about the low standard of the auditionees. Not one has the poise to play the leading role. He is getting ready to leave when Vanda appears: an unbridled and brazen whirlwind of energy. Vanda embodies everything Thomas hates. She is crude, idiotic, and will stop at nothing to get the part. But when Thomas finds himself backed into a corner and lets her try her luck, he is amazed to see Vanda transformed. Not only has she found the right props and costumes, but she understands the character (whose name she shares) intimately, and knows all her lines by heart. The 'audition' lengthens and intensifies, and Thomas' attraction starts to develop into an obsession..."--Container.